The Perception Of Health Cluster Student’s On Health Promoting University In Jambi University - Reskiaddin, La Ode; Putri, Wiya Lulita; Reskiaddin, Muhammad Ridwan (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2025)
Background : Health promoting university is a comprehensive health approach by using universities as a place to create a learning environment that can improve health and well-being in a sustainable manner for academic community, the purpose of this study is to provide an overview related to the perception of jambi university health cluster student to health promoting university. Methods: This research was quantitative research with cross sectional design research. Sampling techniques using purposive sampling. The population in this study was students of faculty of medicine and health sciences of year 2018 and year 2019. Result: The results showed a significant association between students perception of the benefit of health promoting university and the intention of supporting the health promoting university (p=0,000) and there was also a significant relationship between students perception of the barriers to health promoting university and the intention of supporting the health promoting university (p=0,011). Conclusion: This shows that according to Jambi University Health Cluster students, the perception of benefit and perception of barriers on health promoting university is required in order to embody the policies related to health promoting university program.